(untitled) (Raparin Journal of Humanities (RJH), 2026)
Adnan Al-Sayegh is a modern poet, one of the pioneers of modernity and prose poetry, who carries a great deal of pain, alienation, and longing for the land of Iraq. He embodies all this suffering in figurative images of (simile, metaphor, and metonymy), which have the most prominent presence in his poetry. Therefore, our study focused on the figurative language in Adnan Al-Sayegh’s poetry through a rhetorical analysis of his verses, as his poetry is rich in figurative images that convey the creator’s ideas and visions, in addition to faithfully expressing his emotions. This study contributed to examining these images to highlight their rhetorical values, which play a role in deepening the idea and clarifying the meaning. Since the rhetorical aspect does not reveal the beauty of the text without understanding and analyzing it, we turned to critical study to interpret and delve into the analysis of poetic texts. In light of the critical study, poetic texts are interpreted and understood. The research addressed the study of simile through simple and compound similes, as well as metaphor in all its forms. Metonymy was studied through the metonymy of quality, the metonymy of the described, and the metonymy of relation, with poetic texts mentioned for each topic to prove the point and express the poet’s ability to exploit rhetorical arts to present modern conceptual imagery. I relied on the analytical descriptive method to clarify the poetic texts. At the end of the research, the findings were presented, demonstrating how Adnan Al-Sayegh skillfully conveyed his ideas with high capability through his artistic rhetorical tools, which he employed in a way that serves the poetic text.